Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2005
DOI: 10.1093/ejo/cji090
|View full text |Cite
|
Sign up to set email alerts
|

Root resorption associated with orthodontic force in inbred mice: genetic contributions

Abstract: Root resorption (RR) is an unwanted sequela of orthodontic treatment. Despite rigorous investigation, no single factor or group of factors that directly causes RR has been identified. The purpose of this study was to examine the effect of the genotype on susceptibility or resistance to develop RR secondary to orthodontic force. Nine-week-old male mice from eight inbred strains were used and randomly distributed into control (C) or treatment (T) groups as follows: A/J (C = 9,T = 9), C57BL/6J (C = 7,T = 8), C3H/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
51
1
6

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 64 publications
(58 citation statements)
references
References 25 publications
0
51
1
6
Order By: Relevance
“…Measuring by counting cavities per area in histological sections, for instance, is a common approach Al-Qawasmi et al, 2006). In contrast to volumetric measurements, this method does not necessarily give a result of net root resorption, because it could also reflect a change in the turnover of cementum on the surface of the root.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Measuring by counting cavities per area in histological sections, for instance, is a common approach Al-Qawasmi et al, 2006). In contrast to volumetric measurements, this method does not necessarily give a result of net root resorption, because it could also reflect a change in the turnover of cementum on the surface of the root.…”
Section: Discussionmentioning
confidence: 99%
“…Although numerous investigators have suggested associations between genetic factors and root resorption Al-Qawasmi et al, 2003a;AlQawasmi et al, 2003b;Al-Qawasmi et al, 2006;Harris et al, 1997;Ngan et al, 2004) the mechanical environment was an inadequately controlled variable. The current study is the first to appropriately control the mechanical environment and select histological sectioning planes with FEM.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although several studies have investigated this topic, no single or associated factor has been identified as responsible for EARR due to orthodontic treatment. 3 Previous studies focused on the magnitude of the force applied, 1,25 duration, 15,21 and the type of orthodontic treatment 1,6,7 have not established a causal relation between these factors and EARR.…”
Section: Discussionmentioning
confidence: 99%
“…3 The etiology of EARR associated with orthodontic treatment is multifactorial and involves environmental and host factors. Several variables have been described in the literature as possible risk factors for EARR: Tooth anomalies and the shape of root and alveolar bone crest, 13,14,20,27 type and severity of malocclusion, 5 2,3,14 This study investigated the association of age, gender, orthodontic extractions and Angle classification with external apical root resorptions resulting from orthodontic treatment.…”
Section: Introductionmentioning
confidence: 99%